THE USE OF RECIPROCAL TEACHING PROCEDURE IN TEACHING NARRATIVE TEXTS TO IMPROVE STUDENTS’ READING COMPREHENSION - Rizki Maulana Sahab (Journal of English and Education, 2014)
This study was aimed at investigating the implementation of Reciprocal Teaching Procedure (RTP) to improve students’ reading comprehension and finding out the students’ responses toward this method. Reciprocal Teaching Procedure is one of the teaching extensive reading methods that include four strategies: predicting, clarifying, summarizing, and questioning. The quasi-experimental design was utilized in order to collect the data, in which two classes were taken as the samples of this study. The data were collected through pre-test and post-test which were analyzed by using SPSS 20 and ANATES v5 for Windows. The data analysis of the independent t-test showed that there was a significant difference between the post-test means of the control group and the experimental group. Moreover, the data analysis of the dependent t-test showed that there was an improvement of the experimental group’s scores in post-test. Therefore, it could be said that the use of Reciprocal Teaching Procedure was considered effective in improving the students’ reading comprehension. Furthermore, based on the findings of the questionnaire, Reciprocal Teaching Procedure has lots of benefit in teaching reading, such as helping the students to comprehend the text easily, encouraging the students to be more active and communicative in every activity, and improving students’ interest in reading. Thus, it could be concluded that the students’ responses toward the application of Reciprocal Teaching Procedure were positive.